Histological Findings and Predictors of Cerebral Debris From Transcatheter Aortic Valve Replacement: The ALSTER Experience. Issue 11 (10th November 2016) - Schmidt, Tobias; Akdag, Ozan; Wohlmuth, Peter; Thielsen, Thomas; Schewel, Dimitry; Schewel, Jury; Alessandrini, Hannes; Kreidel, Felix; Bader, Ralf; Romero, Maria; Ladich, Elena; Virmani, Renu; et al.
Abstract : Background: Histopathological analyses of debris captured by a cerebral protection system during transcatheter aortic valve replacement have been reported, but the origin of the captured debris was not determined and risk factors were not defined. Methods and Results: Embolic debris was analyzed from 322 filters used in a dual‐cerebral‐filter protection system implemented during transcatheter aortic valve replacement for 161 patients (mean age 81 years, 82 male [51%], logistic EuroSCORE 19% [interquartile range 12–31%]). The debris capture rate was high, with debris from 97% of all patients (156 of 161). No differences by filter location were found (brachiocephalic trunk 86% [139 of 161], left carotid artery 91% [147 of 161]; adjusted P =0.999). Five prevalent types of debris were identified: thrombus (91%), arterial wall tissue (68%), valve tissue (53%), calcification (46%), and foreign material (30%). Female sex ( P =0.0287, odds ratio 1.364, 95% CI 1.032–1.812) and diabetes mellitus ( P =0.0116, odds ratio 1.474, 95% CI 1.089–2.001) were significant risk factors for embolic debris. Additional analysis showed significantly more valve tissue in patients with predilation ( P =0.0294). Stroke and transient ischemic attack rates were 0.6% each (1 of 161). Conclusion: This study showed a high rate of embolic debris consisting of typical anatomic structures known to be altered in patients with aortic stenosis undergoing transcatheter aortic valve replacement. Female patients with diabetes mellitus have increased risk of embolic debris and should be protected by a cerebral protection system during transcatheter aortic valve replacement. Because valve tissue embolizes more often in patients with predilation, procedural planning should consider this finding. Both cerebral arteries (brachiocephalic trunk, left carotid artery) should be protected in the same way.